The Sociolectal and Stylistic Variability of Rhythm in Stockholm. (December 2022) - Young, Nathan J.
The question of "staccato" rhythm in Stockholm's multiethnolect is investigated by comparing nPVIV measurements of the speech of 36 adult male speakers. The men, ages 24–43, come from a stratified sample of social classes and racial groups. Three contextual styles were recorded and analyzed: informal, formal, and very formal. The distribution of nPVIV values in informal speech across class and racial group indicates that speech rhythm splits three ways: low-alternation "staccato" rhythm among the racialized lower-class men, high-alternation rhythm among the white lower-class men, and an intermediate level of rhythm among higher-class men, regardless of racialized category. The "staccato" low-alternation feature is also less stylistically sensitive than the high-alternation feature, implying that the latter is a more established feature than the former. Further, the "staccato" feature is more stylistically sensitive among younger speakers than older speakers, implying an ongoing change from indicator to marker status. For all speakers, age has a stable main effect, which means that younger speakers, independent of racial group and class, have lower alternation than older speakers. Implied here is that low-alternation is a change from below that originates within the racialized working class. While it may be incrementally transmitting into the wider speech community, the white working class is the most resistant to its incursion.